Skin Lesions and Lower Extremity Edema in a newly diagnosed HIV patient - Trotter, Andrew B; Poutsiaka, Debra D (Journal of Advances in Internal Medicine, 2012)
The differential diagnosis of skin lesions in human immunodeficiency virus patients is diverse and includes both infectious and non infectious causes. In this case presentation, a 37 year old male newly diagnosed with HIV presented to a hospital in the United States with skin lesions and worsening lower extremity swelling. After presentation, he developed respiratory distress and was found to have disseminated Kaposi sarcoma with cutaneous and pulmonary involvement. Kaposi sarcoma has decreased in incidence in the era of highly active antiretroviral therapy. However, it remains an important acquired immunodeficiency syndrome defining illness which may be the presenting complaint in a patient with occult HIV infection. Kaposi sarcoma has substantial mortality and morbidity and should be included in the differential diagnosis of skin lesions in a HIV positive patient. DOI: http://dx.doi.org/10.3126/jaim.v1i1.5833 Journal of Advances in Internal Medicine. 2012; 1(1): 12-15